ADMINISTRATION OF POWER 10 SCIENCE PROJECTS BASE ON QUALITY CONTROL CYCLE OF BANCHAUAT SCHOOL UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Pannasak , Somkit; PhrakhruPrachotkitchaphon; Wiraponkan, Boonlert (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research were 1) study the current state of the Power 10 Science Project of Banchauat School. 2). explore management approaches for the Power 10 Science Project based on the quality control cycle of Banchauat School. 3) propose and evaluate the management approach guidelines for the Power 10 Science Project based on the quality control cycle of Banchauat School. This qualitative research collected data through in-depth interviews with 15 stakeholders, expert interviews on the management approach of the Power 10 Science Project with 5 individuals, and a focus group discussions with 7 experts. The data is analyzed using an inductive approach. The results of the study revealed that. 1) Conditions of management of the Power 10 Science Project of Banchauat School. (1) management of learning resource standards found that the school holds meetings with the project committee to plan and organize an environment and resources that support learning. However, the school still lacks some basic scientific equipment and instructional materials, as well as on-site learning resources, which need to be improved to align with the project. (2) management of learning process standards found that the school holds briefing meetings emphasizing that teachers should teach scientific inquiry processes that focus on both methodology and knowledge. The approach integrates science, mathematics, and technology. However, students have different levels of prior knowledge and varying interests, making it challenging to integrate knowledge effectively into learning. (3) management of curriculum standards found that teachers have designed the additional subject Power 10 Science project and student development activities with a variety of tasks that emphasize the integration of science, mathematics, and technology. However, in some activities, students lack analytical thinking and problem-solving skills, making it difficult to integrate knowledge effectively. 2) Administration Guidelines for the Power 10 Science Project based on the quality control cycle of Banchauat School. (1) management of learning resource standards. (2) management of learning process standards (3) management of curriculum standards. The implementation process includes planning meetings, execution according to the plan, evaluation and monitoring, and improvement and development. 3) The presentation and evaluation the administration approach for the Power 10 Science Project based on quality control cycle of Banchauat School. The findings that the approach is appropriate, feasibie, and beneficial. It can be effectively applied to the administration of the Power 10 Science Project based on the quality control cycle of Banchauat School.